The 2nd Entrepreneurship and Management International Conference (EMIC 2011) - Anon (Universiti Malaysia Perlis, 2012)
The 2nd Entrepreneurship and Management International Conference (EMIC 2011) organized by School of Business Innovation and Technopreneurship (PPIPT), Universiti Malaysia Perlis (UniMAP) and Faculty of Business Management, Universiti Teknologi MARA (UiTM), Cawangan Perlis, 17th - 19th December 2011 at Hotel Seri Malaysia Kangar, Perlis, Malaysia.